Backpropagation and Genetic Algorithm in Network Traffic Activities Forecasting - Purnawansyah Purnawansyah (International Journal of Computing and Informatics (IJCANDI), 2017)
This paper presents techniques based on the development of backpropagation (BP) and genetic algorithm models for calculating and analyzing the daily network traffic activities at Universitas Mulawarman, East Kalimantan, Indonesia. The experiment results indicate that a strong agreement between model predictions and observed values, since MAPE is below 5%. Thus, the use of network traffic is becoming a more effective, efficient and optimal. Model optimization is one of future works.